Quantification of flow kinematics using computer-aided visualization - Bajcar, Tom (Strojniški vestnik, 2009)
The paper presents a study of the ability of the visualization methods to measure velocity field in the fluid flow from the concentration field of a passive tracer that is introduced to the fluid. The method is based on the advection diffusion equation. A sequence of successive flow images was processed to obtain the required unknown terms. Concentration of the passive tracer was acquired through greyscale intensity on images at chosen measurement points. Standard numerical procedures were applied to obtain spatial- and time derivatives of the passive tracer concentration. The method was tested in an experiment with an air jet flowing out of a pipe, where the velocity field in a jet was measured with a hotwire anemometer. Comparison of the results of both methods shows good agreement, albeit with certain deviations that are a consequence of simplified approach of the visualization method. The results prove the suitability of the visualization method for quantitative measurements of flow kinematics. Further studies and improvement sof the method could provide a simple and relatively cheap yet reliable tool not only for preliminary assessment of the flow velocity field, but also for velocity measurements in complex flow structures.
Keywords: tok tekočin; vizualizacija; kinematika; tokovi; hitrost; merjenje; merilne metode